2022
DOI: 10.1021/acs.inorgchem.2c00095
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Hydrolytic Stability of the Keggin Molybdo- and Tungsto-Phosphate Anions by Cyclodextrins

Abstract: Keggin-type molybdo-and tungsto-phosphate polyoxoanions are among the most popular polyoxometalates (POMs), but suffer from their limited stability at low pH in aqueous solution. Their superchaotropic properties generate strong supramolecular complexes with cyclodextrins (CDs) which significantly affect the hydrolytic stability of POM. This chaotropically-driven stabilization effect was systematically monitored by 31 P NMR spectroscopy covering a wide range of pH (from 0 to 8) and varying the nature of the CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Fig. 6 51 The evolution of the spectra of γ-CD is very similar to that observed with [PW 12 O 40 ] 3− (see Fig. 5), where H2 and H4 show only a negligible effect by comparison to H3, and to a lesser extent to H5 and H6, experiencing all strong deshielding effects.…”
Section: Dalton Transactionssupporting
confidence: 79%
See 1 more Smart Citation
“…Fig. 6 51 The evolution of the spectra of γ-CD is very similar to that observed with [PW 12 O 40 ] 3− (see Fig. 5), where H2 and H4 show only a negligible effect by comparison to H3, and to a lesser extent to H5 and H6, experiencing all strong deshielding effects.…”
Section: Dalton Transactionssupporting
confidence: 79%
“…11 shows the effect of presence of α-, β-, and γ-CD on the 183 W NMR of [PW 12 O 40 ] 3− . 51 The Keggin POM [PW 12 O 40 ] 3− is characterized by a single sharp 183 W signal at −95.4 ppm corresponding to the 12 W equivalent nuclei of the POM structure (Fig. 11).…”
Section: Use Of Guest Nmr Probesmentioning
confidence: 99%
“…The addition of a base, in contrast, is known to lead to the PW's decomposition as PW is only stable at high acidities ( pH < 2.5). 46,85 The decomposition products of PW (e.g. lacunary POMs, PO 4 3− and WO 4 2− ) exhibit a higher charge density with a higher hydrophilicity and consequently a lower distribution coefficient to hydrophobic alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Native cyclodextrins (CDs) are cheap drug carriers widely used in pharmacology . Recent reports demonstrated that γ-CD, an macrocyclic oligosaccharide built on eight glucopyranose units defining a cavity of 10 Å (Figure ), can host various types of inorganic polynuclear species and even stabilize hydrolytically fragile polyoxometalates and Fe–S clusters in water. The chaotropic effect has been identified as the main contributor of such supramolecular associations, where water solvation plays prominent role in stabilizing these types of hybrid complexation. , [{M 6 X 8 }­L 6 ] n +/– octahedral-cluster-based units represent multifunctional nanosized building blocks composed of a robust {M 6 X 8 } 4+ cluster core (M = Mo or W and X = halides) decorated by six interchangeable apical ligands (L) such as halides, H 2 O, or organic ligands (Figure ). These clusters exhibit both bright phosphorescence in the therapeutic window upon photoirradiation or X-ray irradiation and the ability to photoinduce singlet oxygen production. The photophysical features of [{M 6 Br 8 }­Cl 6 ] 2– and [{M 6 I 8 }­Cl 6 ] 2– cluster-based units make them particularly appealing for biological applications. Nevertheless, the low stability of the octahedral halide molybdenum or tungsten cluster complexes in aqueous media is a serious obstacle to their use in biomedicine.…”
Section: Introductionmentioning
confidence: 99%